"Red is not the only color of a rainbow": The making and resistance of the "MSM" subject among gay men in China. (May 2020) - Liu, Chuncheng
Abstract: Public health scholars classify gay men as "men who have sex with men (MSM)" in their studies and interventions. Debates have been raised about the MSM classification for decades. However, we know little about how people who are classified as MSM perceive and respond to this classification, particularly in the authoritarian context where the biopower interacts with the repressive state power. Drawing upon Ian Hacking's dynamic nominalism theory, this study tries to fill these gaps with interviews of 40 gay men in three Chinese cities about their interactions with public health education materials. I examined their perceptions of MSM knowledge and discourses associated with the classification, as well as their identifications to the MSM subject. I found that, on the one hand, many gay men had internalized the MSM subjectivity and considered themselves essentially at high risk of HIV infection. This compliance was constructed through various biopower techniques with the support of the state's repressive power, as the Chinese state censored almost all public representations of gay men except the HIV/AIDS subject MSM. On the other hand, some of my interviewees were resistant to be part of the MSM classification. I showed how this failure is an unintended consequence of the hegemonic MSM discourse and the authoritarian regime's institutional exclusion of the gay men's community's engagement in the expertise network that develops intervention materials and strategies. At last, I proposed to move beyond the debate around the name and representational character of the MSM by moving toward a more reflexive public health. Highlights: Examines public health classification's symbolic violence on sexual minorities. Argues that "MSM" is more than a linguistic representation but a biopolitical subject. Explores subject-making mechanism that merges biopower with authoritarian repressive power. Discovers the cracks of and resistance to the public health's symbolic violence. Proposes more reflexivity of the production and use of public health knowledge in society.